Across the aisle : opposition in Canadian politics - Smith, David E., 1936-2023 (Toronto [Ont.] : University of Toronto Press, 2013)
"How do parties with official opposition status influence Canadian politics? Across the Aisle is an innovative examination of the theory and practice of opposition in Canada, both in Parliament and in provincial legislatures. Extending from the pre-Confederation era to the present day, it focuses on whether Canada has developed a coherent tradition of parliamentary opposition.
David E. Smith argues that Canada has in fact failed to develop such a tradition. He investigates several possible reasons for this failure, including the long dominance of the Liberal party, which arrested the tradition of viewing the opposition as an alternative government; periods of minority government induced by the proliferation of parties; the role of the news media, which have largely displaced Parliament as a forum for commentary on government policy; and, finally, the increasing popularity of calls for direct action in politics.
Readers of Across the Aisle will gain a renewed understanding of official opposition that goes beyond Stornoway and shadow cabinets, illuminating both the historical evolution and recent developments of opposition politics in Canada."--Pub. desc.
Chapter One: Opposition: 'Somebody Has To Do It' -- PART TWO: PARLIAMENTARY OPPOSITION -- Chapter Two: From Coalition to Coalition, 1867-1920 -- Chapter Three: The Liberal Ascendancy, 1921-1956 -- Chapter Four: Minorities and Majorities, 1957-1992 -- Chapter Five: The Mill of Opposition, 1993-2011 -- PART THREE: CHALLENGES FOR PARLIAMENTARY OPPOSITION -- Chapter Six: Opposition, More or Less -- Chapter Seven: Opposition in the Federation -- Chapter Eight: Whither Parliamentary Opposition? -- PART FOUR: CONCLUSION -- Chapter Nine: The Problem of Parliamentary Opposition Today.
Includes bibliographical references (pages 197-217) and index.
JSTOR
Keywords: Canada. -- Parliament -- Powers and duties; Canada. -- Parliament; Opposition (Political science) -- Canada; Representative government and representation -- Canada; Canada -- Politics and government; Opposition (Science politique) -- Canada; Gouvernement représentatif -- Canada; Canada -- Politique et gouvernement; POLITICAL SCIENCE -- Government -- Legislative Branch; HISTORY -- Canada -- Post-Confederation (1867- ); Legislative power; Opposition (Political science); Politics and government; Representative government and representation; Canada